RECREATIONAL POTENTIAL OF CANINE THERAPY IN A REHABILITATION CENTER FOR CHILDREN AND ADOLESCENTS - Aleksandra Vorozhbitova; Ekaterina Tyuthm (Вестник Северо-Кавказского федерального университета)
The article is the present's results of a study conducted on the basis of GBOSA «Stavropol rehabilitation center for children and teenagers with disabilities» in the group of children with cerebral palsy. The specificity of adaptive motor recreation and its relationship to rehabilitation practice material on canistherapy reveals.